Implementing Unmanned Aerial Vehicles (UAVS) delivery system in the courier services industry: A systematic review and research trends. - Abdul Rahman, Nik Nur Zaheerah; Wan Omar, Wan Marhaini; Md Nasir, Syerina Azlin (International Journal of Accounting, Finance and Business, 2025)
Unmanned aerial vehicles, or drones, are becoming increasingly popular and are impacting package delivery services by presenting both opportunities and challenges. This research aims to explore the potential of UAVs for last-mile deliveries, their capability to reach remote locations, and the new business opportunities they can generate, particularly in the courier services industry. To gain a competitive edge, courier service companies in emerging markets need to be proactive in understanding the key factors contributing to the acceptance of last-mile UAV delivery services. Hence, the goal of this study is to review the existing literature related to UAV implementation in the courier services industry. A systematic review was employed to gain insight and evaluate the literature. The PRISMA review method was utilized to classify the articles obtained from two reputable bibliographic databases, Web of Science and Scopus, resulting in a limited dataset of 64 articles published between 2014 and 2024. The findings revealed that numerous articles were found in the Web of Science database, with the highest number of publications coming from the USA and China. Additionally, most of the articles have been published in International Transactions in Operational Research and Transportation Research Part E: Logistics and Transportation Review. Furthermore, a substantial number of publications are from the business and economics research domain. The study also highlights several research directions to enhance UAV delivery in the courier service industry in the future.